2020
DOI: 10.1002/2211-5463.12965
|View full text |Cite
|
Sign up to set email alerts
|

T‐type calcium channel blockade induces apoptosis in C2C12 myotubes and skeletal muscle via endoplasmic reticulum stress activation

Abstract: Loss of T‐type calcium channel (TCC) function has been reported to result in decreased cell viability and impaired muscle regeneration. In this study, we report a novel mechanism whereby TCC blockade promotes ERS and contributes to Ca 2+ homeostasis disorder of endoplasmic reticulum, thereby resulting in mitochondrial‐related apoptotic cell death in C2C12 myotubes and skeletal muscle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…For instance, calcium release from the endoplasmic reticulum can also induce inner mitochondrial pathway of apoptosis in a variety of cells [ 42 ]. As well, in skeletal muscle cells, T-type Ca 2+ channels can induce endoplasmic reticulum Ca 2+ disorder, contributing to mitochondrial-related apoptosis [ 43 ]. In this regard, the role of Ca 2 + -release channel, ryanodine receptor (RyR) and inositol trisphosphate receptor (IP3R), other than T-type Ca 2+ channels, have been extensively studied in the regulation of apoptosis in different preparations [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, calcium release from the endoplasmic reticulum can also induce inner mitochondrial pathway of apoptosis in a variety of cells [ 42 ]. As well, in skeletal muscle cells, T-type Ca 2+ channels can induce endoplasmic reticulum Ca 2+ disorder, contributing to mitochondrial-related apoptosis [ 43 ]. In this regard, the role of Ca 2 + -release channel, ryanodine receptor (RyR) and inositol trisphosphate receptor (IP3R), other than T-type Ca 2+ channels, have been extensively studied in the regulation of apoptosis in different preparations [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al ( 2020 ) reported that TCC blockade (in C2C12 myoblasts) induced mitochondria‐related apoptosis and reduced mitochondrial transmembrane potential (MMP), induced mito‐ROS generation and enhanced expression of mitochondrial apoptosis proteins.…”
Section: Assessmentmentioning
confidence: 99%
“…They suggested that this highaffinity low-efficacy inhibition may be caused by direct binding of BPA to TCCs in their resting state. Chen et al (2020) reported that TCC blockade (in C2C12 myoblasts) induced mitochondria-related apoptosis and reduced mitochondrial transmembrane potential (MMP), induced mito-ROS generation and enhanced expression of mitochondrial apoptosis proteins. ] reported BPA-related decreased activities of mitochondrial respiratory complexes and abnormalities in mitochondrial morphology in rat cardiac myofibrils, including decreased mitochondrial volume density, reduced cristae density and increased vacuoles, after low-dose BPA (50 μg/kg bw per day) for 48 weeks.…”
Section: Neuromorphologymentioning
confidence: 99%
“…Severe and prolonged ERS leads to cell death. The VGCC inhibitors, verapamil and mibefradil were reported to facilitate cell death via ERS activation in myeloma cells and C2C12 myoblasts [151,152]. Furthermore, progesterone inhibited cell growth and promoted apoptosis via CACNA2D3 in Ishikawa cells [73].…”
Section: Potential Applications Of Calcium Channel Modulators For Cancer Treatmentmentioning
confidence: 99%